Collaborative and argumentative decision support system applied to land use planning - Nawel Boudraa; Djamila Hamdadou (Institute of Advanced Engineering and Science, 2026)
Group decision-making in land-use planning is based on complex processes, due to the diversity of stakeholders and the plurality of criteria to be considered. This article presents the design of a collaborative group decision support system, K-ProSWOT, combining a multi-agent system and multi criteria approaches to support decision-making processes. The methodology combines the K-means clustering algorithm to group similar actions together and reduce the number of options to be studied, the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE II) method for quantitative ranking of possible alternatives, and Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis to structure qualitative collective argumentation. These tools are integrated into a participative process, culminating in a collective, well-argued decision-making process. An interactive dashboard accompanies the system, keeping track of the various stages in the decision-making process. The proposed approach aims to enhance the quality of territorial decisions by reconciling an objective assessment of data with the active involvement of stakeholders.